FACTORS AFFECTING ANDALIMAN EXPORTS IN NORTH SUMATRA PROVINCE - Mulia Maniar Hutapea; Siti Mardiana; Erwin Nyak Akoeb (RADJA PUBLIKA, 2024)
One of the typical spice plants found in North Sumatra is andaliman. Apart from being offered in conventional shops, Andaliman has also penetrated foreign markets. a significant increase in exports is certainly good news and a symbol of hope. The research locations are Laerias District (Dairi Regency) and Raya Haluan District (Simalungun Regency). These two sub-districts are the main andaliman producing sub-districts recorded at the Kuala Namu postal Quarantine Center, Medan. The Andaliman farmers sampled were 135 people consisting of 63 farmers in Dairi Regency and 75 farmers in Simalungun Regency. The research results show that production factors, land area, export prices and local prices do not have a significant effect on the export value of andaliman at the research location which is the main andaliman producing area in North Sumatra province